2015
DOI: 10.1155/2016/5720413
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Treatment Efficiency of Bone Marrow‐Derived Mesenchymal Stem Cell Transplantation via Tail and Portal Veins in CCl4‐Induced Mouse Liver Fibrosis

Abstract: Because of self-renewal, strong proliferation in vitro, abundant sources for isolation, and a high differentiation capacity, mesenchymal stem cells are suggested to be potentially therapeutic for liver fibrosis/cirrhosis. In this study, we evaluated the treatment effects of mouse bone marrow-derived mesenchymal stem cells (BM-MSCs) on mouse liver cirrhosis induced by carbon tetrachloride. Portal and tail vein transplantations were examined to evaluate the effects of different injection routes on the liver cirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 56 publications
4
40
0
2
Order By: Relevance
“…Although statistically insignificant, secretome treatment also reduced the cell viability of HSCs, suggestive of anti-fibrogenic effects of secretome itself. Indeed, several studies have reported the antifibrogenic effects of mesenchymal stem cells or their secretome in the model of liver fibrosis [37][38][39][40][41][42]. Since liver fibrosis process is initiated by inflammation, it appears that secretome reduces the viability of HSCs through anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…Although statistically insignificant, secretome treatment also reduced the cell viability of HSCs, suggestive of anti-fibrogenic effects of secretome itself. Indeed, several studies have reported the antifibrogenic effects of mesenchymal stem cells or their secretome in the model of liver fibrosis [37][38][39][40][41][42]. Since liver fibrosis process is initiated by inflammation, it appears that secretome reduces the viability of HSCs through anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…After that, the laboratory made various achievements in the development of new technologies for isolation, characterization, differentiation, and cryopreservation of various stem cells from different tissues, including adipose tissue, umbilical cord blood, and bone marrow [31][32][33][34][35]. This laboratory succeeded to differentiate MSCs into adipocytes, osteoblasts, chondrocytes, cardiomyocytes, insulin-producing cells, and neuron-like cells [36][37][38][39]. Moreover, various animal models of different diseases were also developed in order to execute pre-clinical trials [32,37,40].…”
Section: Stem Cell Milestone In Viet Nammentioning
confidence: 99%
“…This laboratory succeeded to differentiate MSCs into adipocytes, osteoblasts, chondrocytes, cardiomyocytes, insulin-producing cells, and neuron-like cells [36][37][38][39]. Moreover, various animal models of different diseases were also developed in order to execute pre-clinical trials [32,37,40]. The animal disease models treated by stem cell transplantation have included femoral head necrosis, type 1 and 2 diabetes mellitus [32], bone marrow failure, injured knee cartilage [41], aged skin, liver cirrhosis [37], hindlimb ischemia [42,43], heart failure [44], and spinal cord injury [45].…”
Section: Stem Cell Milestone In Viet Nammentioning
confidence: 99%
See 1 more Smart Citation
“…Fixed samples were embedded in paraffin, sectioned into 5µm-thick slices and stained with Hematoxylin/Eosin (Sigma-Aldrich) and Trichrome (Sigma-Aldrich), according to previous protocols (Truong et al, 2016). Immunohistochemistry of the sections was also done according to previous protocols (Truong et al, 2016).…”
Section: Histologymentioning
confidence: 99%